Effect of vision therapy on measures of oculomotor function of patients presenting with post-concussion syndrome - Rollett, Paul; Morandi, Garrett (Canadian Journal of Optometry, 2019)
Oculomotor dysfunction is a common symptom of post-concussion syndrome (PCS). By use of a retrospective analysis approach, the efficacy of Vision Therapy (VT) for the treatment of PCS related symptoms of the visual system was investigated. Overall, 56 patients were selected for inclusion in this study, all of which presented with clinical impairment of at least one measure of oculomotor functioning. Activities related to VT were wide-ranging and case-dependent, but all aimed to improve one of the five main areas of visual function. Following completion of VT, all patients demonstrated statistically or clinically significant improvements, as defined by use of Morgan’s Norms, in at least one measure of oculomotor functioning related to PCS. In general, improvements in measures of oculomotor functioning were greatest for near point of convergence, vergence facility and accommodative facility. Patients receiving 20 sessions of VT had improved and less variable outcomes when compared to those receiving 5-10 sessions of VT. In addition, VT was found to improve symptoms of visual discomfort in patients presenting with PCS. Results of this retrospective analysis demonstrate significant improvements in measured outcomes for all patients receiving VT and support VT as a treatment option for symptoms of PCS.